Template-assisted growth of nanoporous VTTBNc films: Morphology and moisture sensitivity studies - Aziz, Fakhra; Bakar, Azlinda Abu; Ahmad, Zubair; Bawazeer, Tahani M.; Alsenany, Nourah; Alsoufi, Mohammad S.; Supangat, Azzuliani (Elsevier, 2018)
A novel structured of nanoporous vanadyl 2,11,20,29-Tetra Tert-Butyl 2,3 Naphthalocyanine (VTTBNc) films were prepared by template-assisted method. The structure and morphology of the fabricated VTTBNc nanostructures were studied by field emission scanning electron microscopy (FESEM) and micro-Raman spectroscopy. The VTTBNc nano-porous films showed a potential application in humidity sensors.